Mechanisms of Ischemic Heart Disease Development in Type 2 Diabetes Patients Based on Renal Function - Georgii B. Mankovskyi; Yevhen Yu. Marushko; Yana Yu. Dzhun; Oleksandr S. Stychynskyi (Український журнал серцево-судинної хірургії)
Ischemic heart disease (IHD) remains a leading cause of mortality and disability in Ukraine and globally, primarily due to stenosing atherosclerosis of the coronary arteries. Type 2 diabetes mellitus (T2DM) is a significant factor accelerating atherogenesis, alongside with chronic kidney disease. Investigating the causes of myocardial ischemia in patients with IHD, T2DM, and cardio-renal-metabolic syndrome requires further exploration.